Analysing the Impact of Service Quality on Brand Image and Brand Advocacy - 김정민; 이수경; 신리현; 박진우 (Journal of distribution science, 2024)
Purpose: This study aims to enhance airport service quality by examining their impact on brand image, advocacy, and mediating brand trust in the aviation service distribution sector. Research Design, Data, and Methodology: Using existing literature, we propose a structural model exploring the relationships between key components which are service quality, brand trust, brand Image and brand advocacy. An online survey, based on prior literature, was administered to 287 Koreans who have experienced using facilities or services at Incheon International Airport (IIA). Statistical analysis employed confirmatory factor analysis (CFA) and structural equation modelling (SEM). Results: Research findings show significant impacts of airport service quality on brand trust. Increased brand trust positively influences airport brand image and advocacy. Conclusion: The study emphasizes the aviation industry's potential to boost brand trust through improved airport service quality via users’ interactions. Service quality is critical factors in building brand trust. The findings emphasize the critical role of service quality in fostering brand trust. It underscores the importance of user's satisfaction with service quality in fostering brand trust which can lead to brand image and brand advocacy. The aviation industry should formulate policies and strategies to enhance brand trust improved service quality, thereby improving brand image and brand advocacy. KCI Citation Count: 0